Zastosowanie rozmytych wielokryterialnych metod porządkowania liniowego do konstrukcji syntetycznego miernika poziomu rozwoju powiatów - Wysocki, Feliks; Łuczak, Aleksandra (Application of Fuzzy Multi-Criteria Linear Classification Methods to Construction of Synthetic Measure of Counties Development, 2005)
The aim of this paper was to investigate the applicability of the fuzzy multicriteria classification methods to the construction of synthetic characteristics. The method proceeds from the erection of a hierarchic structure for the examined multicriteria problem and utilizes linguistic variables and trapezoidal fuzzy numbers to rate basic characteristics and criteria for each decision element. The proposed procedure was employed to assess the socio-economic development of rural Wielkopolska seen as a collection of counties.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu. Taksonomia (12); 2005; nr 1076, s. 190-199